2018
DOI: 10.2460/ajvr.79.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term anti-inflammatory glucocorticoid treatment on clinicopathologic, echocardiographic, and hemodynamic variables in systemically healthy dogs

Abstract: OBJECTIVE To investigate mechanisms by which anti-inflammatory doses of orally administered intermediate-acting glucocorticoids (prednisone) could predispose dogs to progression of heart disease or congestive heart failure. ANIMALS 11 client-owned dogs with allergic dermatitis and 11 matched healthy control dogs. PROCEDURES Clinicopathologic, echocardiographic, and hemodynamic variables were measured. Dogs with allergic dermatitis then received prednisone (1 mg/kg, PO) once daily for 14 consecutive days beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
3
29
0
1
Order By: Relevance
“…It has been reported that lymphocyte counts were significantly decreased compared to those of healthy control dogs after two weeks of antiinflammatory doses of prednisone therapy (Moore et al, 1992). However, it is reported that prednisone administration to healthy dogs with allergic dermatitis caused no significant changes in lymphocyte concentration (Masters et al, 2018). In this study, eight dogs treated with prednisolone prior to sampling had lower lymphocyte concentrations (median 555 cells/µl; ranged between 0-1944 cells/µl) compared to the remaining dogs (median 1395 /µl; ranged between 0-12376 cells/µl).…”
Section: Discussionmentioning
confidence: 52%
“…It has been reported that lymphocyte counts were significantly decreased compared to those of healthy control dogs after two weeks of antiinflammatory doses of prednisone therapy (Moore et al, 1992). However, it is reported that prednisone administration to healthy dogs with allergic dermatitis caused no significant changes in lymphocyte concentration (Masters et al, 2018). In this study, eight dogs treated with prednisolone prior to sampling had lower lymphocyte concentrations (median 555 cells/µl; ranged between 0-1944 cells/µl) compared to the remaining dogs (median 1395 /µl; ranged between 0-12376 cells/µl).…”
Section: Discussionmentioning
confidence: 52%
“…Other long‐term adverse effects include alopecia; thin skin; calcinosis cutis; susceptibility to bruising; muscle atrophy; fat redistribution to the abdomen with a resulting pot‐bellied appearance; hepatomegaly; predisposition to pyoderma, demodicosis, and urinary tract infections; and exacerbation of congestive heart failure . Predisposition to diabetes mellitus and pancreatitis also is suspected to be associated with chronic glucocorticoid treatment .…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…hepatomegaly; predisposition to pyoderma, demodicosis, and urinary tract infections; and exacerbation of congestive heart failure. 66 Predisposition to diabetes mellitus and pancreatitis also is suspected to be associated with chronic glucocorticoid treatment. [67][68][69] Commonly observed clinicopathologic abnormalities include a stress leukogram and increased serum alkaline phosphatase (ALP) activity, with occasional polycythemia, thrombocytosis, hyperlipidemia, and hyperglycemia.…”
Section: Rationalementioning
confidence: 99%
“…In the current study, the increase in heart size was likely due to volume expansion secondary to mineralocorticoid effects since there was no significant change in BG concentration with steroid treatment. Blood pressure was not significantly different after steroid treatment and systemic hypertension does not seem to be a clinically relevant effect of steroids administered PO in cats as in dogs . Total solids concentration significantly increased after steroid treatment and might be due to increased hepatic synthesis of albumin or increased circulating lipids .…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, glucocorticoid and mineralocorticoid receptors on vascular smooth muscle mediate vasoconstriction by affecting transmembrane sodium and calcium flux in canine and lapine arteries, and therefore steroid therapy might increase vascular resistance . Increased systemic blood pressure is associated with a short course of steroids administered PO in dogs . Thus, increased plasma volume, hypertrophy‐associated diastolic dysfunction, and increased afterload due to enhanced systemic vascular resistance are all mechanisms by which steroids might predispose a cat to develop congestive heart failure (CHF).…”
Section: Introductionmentioning
confidence: 99%